Demographics, Economics and Psychographics Determinants of Life Insurance Consumption among School Teachers in Kampar, Perak - Bakar, Juliana Abu; Ganapathy, Thavamalar ap; Krishnan, Chitrah a/p (International Journal of Engineering and Technology, 2018)
Life insurance has become a stable and progressive market keep improving as one of the key financial pillars in Malaysia. However, current consumption rate of 55.5% is considered low and there were more prospects for life insurance companies to grow in suburban and rural areas as the concentration now is more in urban areas. Thereby, there is a need to extend and focus on the rest of uninsured population at which high proportion to be concentrated on both suburban and rural areas. This study aims to determine demographics, economics and psychographics factors that influence consumer purchasing decisions of life insurance among 1,256 school teachers in Kampar district. The stratified random sampling technique applied in order to select the respondents for this study and the data has been analyzed by using multiple regression model. The justification for selecting this technique is to ensure that all schools in Kampar district have its representative.Â This study found that personality behavior in psychographic factor is positively and significant determinant of life insurance consumption among school teachers in Kampar District. This study will significant towards growth of insurance industry, whereby it wills benefits governmental or non-governmental agencies.